Rozbor filmu - Kokeš, Radomír D., 1982- (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2015)
The aim is to offer a comprehensive textbook focused on formal analysis of stylistic, narrative, and thematic arrangement of a film work. The publication should be useful for students of film studies and audio-visual culture, as well as for wide audiences (academics, film reviewers, and film fans). The book structure follows a bottom-up explanation model which starts with searching for a research problem and the thesis formulation and goes on to questions related to the text outline and the structure of argumentation. The final part of the book offers more complex film case analyses rooted in the perspective of the previous chapters.